Discussion of Feng et al. (2014). "Statistical reconstruction of two-phase random media" [Comput. Struct. 137 (2014) 78–92]. (15th January 2016) - Shields, Michael D.; Bocchini, Paolo; Deodatis, George
Highlights: Clarifies misrepresentations of existing iterative methods in Feng et al. Demonstrates the efficiency of the ITAM method for random media simulation. Addresses compatibility and generality of random media simulation methods. Abstract: The recent work of Feng et al. (2014) presents a new approach for generation of 2-phase random media using a translation-based stochastic field. The method is useful, elegant, and efficient. The intention of this discussion is to clarify some misrepresentations of prior work as they are presented in terms of the efficiency of iterative methods and the Iterative Translation Approximation Method (ITAM) of Shields et al. (2011) specifically. The ITAM approach is far more efficient than presented and represents a negligibly small increase in expense over the proposed approach. Some issues pertaining to compatibility and generalization of translation fields are also discussed.